Determination of Product Distribution Allocation in Pharmaceutical: a Case Study - Lenny Lidiawaty; Ratih Dyah Kusumastuti (Eduvest - Journal of Universal Studies, 2025)
Pharmaceutical distribution companies operate under tight profit margins and face increasing expectations to adopt environmentally sustainable practices. In Indonesia, companies like PT XYZ manage complex, multi-node distribution networks that supply pharmaceutical products nationwide. This complexity presents challenges in optimizing allocation decisions that address both operational efficiency and environmental sustainability. This study aims to develop a multi-objective optimization model that minimizes both total distribution costs and carbon emissions. The model is constructed using operational data from PT XYZ’s enterprise resource planning (ERP) system for 2024. The optimization employs a weighted sum approach with minimum deviation to achieve an optimal trade-off between distribution cost and carbon emissions. This approach is evaluated under constraints related to warehouse capacity, transporter load limits, delivery timeliness, and product integrity. The results indicate that model produce efficient distribution patterns, the minimum deviation method provides a more balanced trade-off between cost and environmental impact. This outcome is especially relevant for companies seeking to align logistics performance with sustainability objectives. By integrating financial and environmental goals into a unified decision-making framework, this study provides a practical solution for pharmaceutical logistics planning. It offers strategic insights into optimizing delivery networks, selecting transport modes, and evaluating the environmental implications of distribution decisions.